Determination of Heavy Metals in Food Products (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The article considers data on the solubilization of heavy metals in beef meat in the form of aqueous extracts, ensuring the complete separation of heavy metals in meat, potentiometric oximetric titration of the amount of mercury, cadmium, lead and iron in beef meat with a U-130 ion meter and spectrophotometric determinations were evaluated on a spectrophotometer KFK-3.